A novel aptamer-based DNA diamond nanostructure for in vivo targeted delivery of epirubicin to cancer cells. Issue 25 (7th March 2017) - Abnous, Khalil; Danesh, Noor Mohammad; Ramezani, Mohammad; Lavaee, Parirokh; Jalalian, Seyed Hamid; Yazdian-Robati, Rezvan; Emrani, Ahmad Sarreshtehdar; Hassanabad, Koroush Yousefi; Taghdisi, Seyed Mohammad
Abstract : The clinical administration of epirubicin (Epi) in the treatment of cancer has been restricted, owing to its cardiotoxicity. Abstract : The clinical administration of epirubicin (Epi) in the treatment of cancer has been restricted, owing to its cardiotoxicity. Targeted delivery of anticancer agents could increase their therapeutic efficacy and decrease their off-target effects. In this study, a novel Epi-DNA diamond nanostructure (DDN) conjugate containing two kinds of aptamers (MUC1 and ATP aptamers) was designed and evaluated in the treatment of target cells, including C26 cells (murine colon carcinoma cell) and MCF-7 cells (breast cancer cell). DDN and Epi-DDN conjugate formations were analyzed by gel retardation assay and fluorometric analysis, respectively. Release profiles of Epi from the developed Epi-DDN conjugate were evaluated at pHs 5.4 and 7.4. For the MTT assay (cell viability study), CHO cells (Chinese hamster ovary cell, nontarget), C26 and MCF-7 cells (target) were treated with the Epi-DDN conjugate, DDN, Epi, Epi-DDN conjugate without ATP aptamer and Epi-DDN conjugate without MUC1 aptamer. Internalization of the Epi-DDN conjugate was assessed by flow cytometry analysis and fluorescence imaging. Finally, the designed Epi-DDN conjugate was utilized for inhibition of tumor growth in vivo . 10 μM Epi was efficiently loaded in 1 μM DDN. The drug was released from the Epi-DDN conjugate in a pH-sensitive manner (higher release in acidic conditions). The results of flow cytometry analysis and fluorescence imaging confirmed that the developed Epi-DDN conjugate was effectively internalized into target cells, but not into nontarget cells. The results of the MTT assay were consistent with the internalization data. The Epi-DDN conjugate had more cytotoxicity in MCF-7 and C26 cells and less cytotoxicity in CHO cells in comparison with Epi alone. Moreover, the Epi-DDN conjugate could effectively prohibit tumor growth in vivo .